Pomoc na zatrudnienie i szkolenia jako jedna z kategorii pomocy publicznej - Bartniczak, Bartosz (Aid to Employment and Training as one of Categories of State Aid, 2008)
In 2005 the European Commission started working on preparing reform of state aid granting rules in the European Union. One of the factors which determined that this reform is the necessity of reorientation of state aid to the horizontal designation. The main aim of the article is to show the role of state aid in supporting training and employment. The article presents law regulation link with granting state aid for this aim. The main subjects giving state aid in this area are the State Fund for Disabled Persons Rehabilitation and Voluntary Labor Corps. The article shows the role which these subject splay-sin granting state aid. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 37-46